Carveol Attenuates Seizure Severity and Neuroinflammation in Pentylenetetrazole-Kindled Epileptic Rats by Regulating the Nrf2 Signaling Pathway. (12th August 2021) - Alvi, Arooj Mohsin; Al Kury, Lina Tariq; Alattar, Abdullah; Ullah, Ikram; Muhammad, Asmaa Jan; Alshaman, Reem; Shah, Fawad Ali; Khan, Arif Ullah; Feng, Jinxing; Li, Shupeng
Abstract : Epilepsy is a neurodegenerative brain disorder characterized by recurrent seizure attacks. Numerous studies have suggested a strong correlation between oxidative stress and neuroinflammation in several neurodegenerative disorders including epilepsy. This study is aimed at investigating the neuroprotective effects of the natural compound carveol against pentylenetetrazole- (PTZ-) induced kindling and seizure model. Two different doses of carveol (10 mg/kg and 20 mg/kg) were administered to male rats to determine the effects and the effective dose of carveol and to further demonstrate the mechanism of action of nuclear factor E2-related factor ( Nrf2 ) in PTZ-induced kindling model. Our results demonstrated reduced levels of innate antioxidants such as superoxide dismutase (SOD), catalase, glutathione-S-transferase (GST), and glutathione (GSH), associated with elevated lipid peroxidation (LPO) and inflammatory cytokines level such as tumor necrosis factor-alpha (TNF- α ), and mediators like cyclooxygenase (COX-2) and nuclear factor kappa B (NF κ B). These detrimental effects exacerbated oxidative stress and provoked a marked neuronal alteration in the cortex and hippocampus of PTZ-intoxicated animals that were associated with upregulated Nrf2 gene expression. Furthermore, carveol treatment positively modulated the antioxidant gene Nrf2 and its downstream target HO-1 . To further investigate the role of Nrf2, an inhibitor of Nrf2 called all-trans retinoic acid (ATRA) was used, which further exacerbated PTZ toxicity. Moreover, carveol treatment induced cholinergic system activation by mitigating acetylcholinesterase level which is further linked to attenuated neuroinflammatory cascade. The extent of blood-brain barrier disruption was evaluated based on vascular endothelial growth factor (VEGF) expression. Taken together, our findings suggest that carveol acts as an Nrf2 activator and therefore induces downstream antioxidants and mitigates inflammatory insults through multiple pathways. This eventually alleviates PTZ-induced neuroinflammation and neurodegeneration.